2014
DOI: 10.1080/1533256x.2014.958492
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the Black Box From Within: Stakeholder Perspectives on Family Drug Court Best Practices

Abstract: This article describes a mixed-methods, concept mapping study in an urban family drug court (FDC) designed to identify keys to FDC success from stakeholders' perspectives. Participating FDC team members and clients developed a set of items they deemed integral to an FDC, thematically clustered the items, and then rated their relative importance. Using these data, cluster analysis and multidimensional scaling generated 6 themes perceived as contributing to positive outcomes. Resultant concept maps revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Studies conducted of specialty Family Courts, which are generally perceived as being more attuned to parent voice, participation and understanding, have resulted in mixed findings. A study of urban Family Drug Court clients showed that parents prioritized the individual-judge relationship (e.g., having a caring judge, having direct communication with the judge) and the court's interpersonal and structural support (e.g., providing a supportive atmosphere, providing clear and detailed court direction to all involved parties) (Lloyd, Johnson, & Brook, 2014). However, parents' perceptions of their actual experiences with judges varied.…”
Section: Parents' Lived Experiences Of Family Courtmentioning
confidence: 99%
“…Studies conducted of specialty Family Courts, which are generally perceived as being more attuned to parent voice, participation and understanding, have resulted in mixed findings. A study of urban Family Drug Court clients showed that parents prioritized the individual-judge relationship (e.g., having a caring judge, having direct communication with the judge) and the court's interpersonal and structural support (e.g., providing a supportive atmosphere, providing clear and detailed court direction to all involved parties) (Lloyd, Johnson, & Brook, 2014). However, parents' perceptions of their actual experiences with judges varied.…”
Section: Parents' Lived Experiences Of Family Courtmentioning
confidence: 99%
“…For example, an FTC judge is expected to ask participants about their children and families, discuss with the participant new parenting or family skills they have learned, reinforce safe and consistent parenting, listen to resolve ongoing parenting challenges, and discuss therapeutic progress the participant observes in their children or other family members (CCFF & NADCP, 2019). Time and again, FTC participants report that their relationship with the judge is a critical factor in their engagement and success in the program (Ashford, 2004(Ashford, , 2006Lloyd, 2015b;Lloyd, Johnson, & Brook, 2014). Participants describe the positive impact of their judge's caring, concern, and fairness (Fessinger et al, 2020;Lloyd, 2015a;Lloyd et al, 2014).…”
Section: Standard 2: Role Of the Judgementioning
confidence: 99%
“…Time and again, FTC participants report that their relationship with the judge is a critical factor in their engagement and success in the program (Ashford, 2004(Ashford, , 2006Lloyd, 2015b;Lloyd, Johnson, & Brook, 2014). Participants describe the positive impact of their judge's caring, concern, and fairness (Fessinger et al, 2020;Lloyd, 2015a;Lloyd et al, 2014). In a family-centered setting, these interactions include attention to the participant as a parent, spouse or partner, and family member.…”
Section: Standard 2: Role Of the Judgementioning
confidence: 99%
“…Drug court professionals recognized the importance of sharing participants’ relevant information for addressing their needs and service planning (Korchmaros et al, 2016), and drug court teams and the presiding judges need to consider the probative evidence when making decisions on treatment or timely sanctions (NADCP, 2015a). Across the board, drug court professionals consider communication as one of the most critical components for drug court success (Frazer, 2006; Gallagher, Nordberg, & Kennard, 2015; Lloyd, Johnson, & Brook, 2014). Sharing information about participants’ progress promptly will help drug court teams to deliver a consistent message to the participants and to prevent participants from selectively submitting different information to different team members (NADCP, 2015a).…”
Section: Challenges Of Collaboration and Model Adherencementioning
confidence: 99%